2018
DOI: 10.1021/jacs.8b10396
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Assemblies from J-Aggregated Dyes: A Stimuli-Responsive Tool Applicable To Living Systems

Abstract: Controlling the packing arrangements of dyes is a facile way of tuning their photophysical and/or photochemical properties, thus enabling new sensing mechanisms for photofunctional tools. Here, we present a general and robust strategy toward water-stable J-aggregated dye-templated nanoassemblies by incorporating an amphiphilic diblock copolymer and a stimuli-responsive dye as the only two building components. An iodo-substituted boron dipyrromethene (BODIPY) was adopted as a template to direct the self-assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 65 publications
(83 reference statements)
6
81
0
Order By: Relevance
“…For Br⋅⋅⋅π bond, the distance of bromine atom to the centroid of BODIPY core, d Br⋅⋅⋅π , is 3.753 Å, and the angle φ is 96.85° (Figure b), and those for Cl⋅⋅⋅π bond are 3.756 Å and 99.00° (Figure d), respectively, within the criteria for X⋅⋅⋅π interactions . Notably, π‐stacking interaction also existed in the BODIPY J‐dimer as in other reported BODIPY J‐aggregates . Collectively, the halogenated BODIPY dimerized in an antiparallel manner on the formation of a π–π bond and dual X⋅⋅⋅π halogen bonds as shown in Figure b, d and also illustrated in Figure c.…”
Section: Figuresupporting
confidence: 68%
See 2 more Smart Citations
“…For Br⋅⋅⋅π bond, the distance of bromine atom to the centroid of BODIPY core, d Br⋅⋅⋅π , is 3.753 Å, and the angle φ is 96.85° (Figure b), and those for Cl⋅⋅⋅π bond are 3.756 Å and 99.00° (Figure d), respectively, within the criteria for X⋅⋅⋅π interactions . Notably, π‐stacking interaction also existed in the BODIPY J‐dimer as in other reported BODIPY J‐aggregates . Collectively, the halogenated BODIPY dimerized in an antiparallel manner on the formation of a π–π bond and dual X⋅⋅⋅π halogen bonds as shown in Figure b, d and also illustrated in Figure c.…”
Section: Figuresupporting
confidence: 68%
“…Two halogenated BODIPY dyes, that is, BDP‐Cl and BDP‐Br , and a halogen‐free analogue, BDP‐H , were synthesized according to the procedures as shown in Scheme S1 (see the Supporting Information). In organic solvent, such as acetone, the three BODIPYs were dissolved in the monomer form, which was reflected by the typical monomer absorption band (Figures a, c, and S1a) . Upon adding water to the acetone solution of BDP‐Cl or BDP‐Br to a critical water fraction of 70 or 60 %, a red‐shifted absorption band emerged at about 786 nm, suggesting J‐aggregation of BODIPYs (Figures a, c, S2a, and S3a) .…”
Section: Figurementioning
confidence: 97%
See 1 more Smart Citation
“…As illustrated in Scheme , azide‐functionalized PS Se‐I ( azide PS Se‐I ) was synthesized. The flexibility of the click chemistry and phenolic hydroxy protecting‐group chemistry enabled us to prepare a triphenylphosphonium cation (TPP; mitochondria‐targeting group) functionalized aPS ( mito‐PN PS ) containing peroxynitrite‐responsive arylboronate as the triggerable moiety (Scheme ; see the Supporting Information). mito‐PN PS was very stable in PBS (see Figure S23), and was instantly converted into mito PS in the presence of OONO − (Scheme ), as evidenced by a recovery of the visible absorption of mito PS (Figure a; see Figure S24).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the design of BODIPY based aggregates important for clinical research, photodynamic therapy and biomedical applications ( Figure 23). [94] Huang et al, reported the quick response of selenoxide portray under oxidising/reducing agents induces the amphiphilicity property and further reduced to selenide moiety by vitamin C. Selenium/pillar [5]arene exhibits vesicles in water and noncyclic monomer/pillar [5]arene formed micelles, however, both morphology were destroyed on addition of vitamin C. Later, micelles and vesicles regenerated with H 2 O 2 indicates the possibility of reversible self-assembly employed in targeted drug delivery of doxorubicin (DOX). [95] Another report suggested that the redox responsive property from host/guest complex- ation of selenium/pillar [6]arene/ferrocenium wherein ferrocene played vital role.…”
Section: Chemical and Heat Responsive Smart Materials: Applications Fmentioning
confidence: 99%